Desarrollo de un prototipo piloto de módulo eco-amigable para recarga de energía e interacción (2021)
The development of this project shows the development of a prototype (eco-friendly kiosk), which includes solar photovoltaic modules for the recharge of electronic devices, which can be powered both by USB inputs and by a 110 Volt power outlet. The kiosk prototype has also its own LED lighting system. This prototype helps with the removal of the carbon footprint because it does not use any other type of energy besides sunlight, in addition to this, by implementing sensors of air quality, temperature and humidity, the user who uses this eco-friendly kiosk will have knowledge about the air around them and the environmental conditions surrounding the place while staying there. The amount generated power will also be monitored through the use of voltage and current sensors. The development of this prototype gives rise to a new generation of studio or outdoor recreation modules located in open spaces, because being self-sustaining and presenting a functional electrical system for the recharge or use of electronic devices makes them suitable for these types of activities